An application of Lagrangian relaxation approach in reverse logistics problem - Lamsali, Hendrik (Scientific & Academic Publishing Co., 2013)
This research examines the reverse logistics problem in which manufacturers need to determine the collection methods for used product at the end of its life. Three collection methods are studied namely pick-up, drop-off and mail return. The research investigates the problem of assigning appropriate collection methods that can maximize manufacturer’s profit. Initially, a mixed integer non-linear programming model integrating the three collection methods is proposed to tackle the problem. In the later part, a Lagrangian heuristic approach is then proposed due to the complexity of the problem and the inability of the previous solution method to solve larger problem instances effectively.The proposed solution is tested using some problem instances and the results are promising.The issues, potential and benefits of the proposed solution are highlighted.